Exploration of Ethnomathematics in the Design of Mandailing Natal Traditional Houses as a Learning Resource - Agustina Rangkuti; Machrani Adi Putri Siregar (Jurnal Pendidikan Matematika IKIP Veteran Semarang, 2023)
Education and culture are inseparable, much like two sides of a coin. Ethnomathematics emerges to bridge the gap between education and culture, particularly in the context of mathematics learning. Surprisingly, without realizing it, the Mandailing community has long been applying mathematical concepts, as can be seen in the architecture of the Bagas Godang in Mandailing Natal. The aim of this research is to explore and describe the mathematical concepts found in the structure and ornaments of the Bagas Godang. This study adopts a qualitative research design with an ethnographic approach. The elements of the building, such as fences, windows, roofs, roof ornaments, house structure, pillars, and stairs in the Bagas Godang, contain mathematical concepts, namely geometry and odd numbers, which can be utilized as a means of teaching mathematics.